Molli and Max in the future [videorecording (Blu-Ray)] - Litwak, Michael Lukk; Mamet, Zosia, 1988-; Athari, Aristotle; Burstein, Danny; Castro, Arturo, 1985- (Level 33 Entertainment, 2024)
A sci-fi rom-com about a man and woman whose orbits repeatedly collide over the course of 12 years, 4 planets, 3 dimensions and 1 space-cult. Molli and Max in the Future takes the character-driven romance of When Harry Met Sally and combines it with an eclectic sci-fi universe like Futurama. Classic practical effects combined with cutting edge technology create Molli and Max's unique universe.